Blogging: A way to foster EFL writing - Quintero, Luz Mary (Colombian Applied Linguistics Journal, 2008)
This article reports on the results of an action-research project carried out with a group of first year university students from an “English Program” at a public university in Bogotá. The project aimed to gain insights into EFL writing and to analyze the role that feedback played in the process of writing. The experience was implemented through the interaction of two groups of students, one from Colombia and the other from Canada, who interacted regularly by means of using blogs. Students were provided with three different spaces: a personal blog in which they wrote about topics of personal interest, a group blog that allowed students to work and write cooperatively, and a debate blog that required the use of argumentative writing. The findings of this research suggest that EFL writing is greatly developed when students feel part of a community to interact with and to share similar interests and language learning goals which are mediated, in this case, by technology. It was also found that by writing in blogs students not only developed their writing but more importantly, students have the possibility to portray and show their own selves through the written pieces they post. Finally, the feedback was found to be beneficial in EFL writing as it was a crucial ingredient that gave student-writers tools to scaffold in the writing process.